Testing of the efficacy of dietary natural and synthetic antioxidants on broiler performance: A comparative study - Ahmed, S. Kh.; Abdul-Abass, M. H.; Al-Hammed, S. A. (International Journal of Agricultural Technology, 2015)
A comparative study was conducted to test of the efficacy of dietary natural and synthetic antioxidants on productive performance, blood biochemical composition and liver oxidation status of broiler chickens. One-day old Ross broiler chickens(n=210)were fed together on basal diet during the first week of age, then divided randomly into seven treated groups:T0(control group) without any addition,T1=0.75g Withania somnifera leaves(WSL)/kg diet,T2=1.5gWSL/kg diet,T3=0.75g rosemary leaves(RL)/kg diet,T4=1.5gRL/kg diet,T5=0.75g vitamin E/kg diet and T6=1.5g vitamin E/kg diet. Results showed that supplementing broilers with 1.5g WSL significantly increased final live body weight, body weight gain, dressing percentage and improved feed conversion ratio. Results of serum biochemical tests indicated that dietary supplementation with natural and synthetic antioxidants significantly (p≤0.05) reduced serum cholesterol as compared to control group. High levels of RL and vitamin E significantly decreased LDL as compared to control. Dietary supplementation with 1.5g RL significantly decreased serum albumin and glucose and increased globulin as compared to vitamin E supplemented groups. No significant differences were found between all experimental groups in serum HDL, VLDL, triglycerides, total protein, AST and ALT. In liver,1.5g WSL significantly reduced peroxide value and malondialdehyde levels as compared to RL. It can be concluded from this study that adding herbs like Withania somnifera as natural antioxidant to broiler diet had positive effect in reducing lipid oxidation and minimize harmful effect of oxidation damage.